Effectiveness of public service program related cocoa fermentation sop in increasing the knowledge of cocoa farmer - Hanif Alamudin Mansur; Noor Harini; Elfi Anis Saati; D. Damat; W. Warkoyo; S. Sukardi; Vritta Amroini Wahyudi; Rista Anggriani; Devi Dwi Siskawardani; Afifah Husna; Desiana Nuriza Putri; Nafidzah Nur; Ayu Lestari (Journal of Community Service and Empowerment, 2023)
Cocoa farmers in this area were not familiar with post-harvest processing, usually, the cocoa bean was sold directly without any fermentation. This public service objective provides information on good quality control of cocoa plant beans, such as fermentation pH, sorting, and contained water content. Followed to improve the knowledge about fermented cocoa bean's characteristics, especially about fine flavor cocoa (FFC) which has a flavor profile and also several active compounds for healthy. Data collection was carried out by filling out questionnaires from 25 farmer respondents. The results of the service showed that as many as 52% of the respondents have been cocoa farmers for more than 5 years. Most of the cocoa farmers produced more than 500 kg/harvest. Many farmers do not ferment cocoa beans because the fermentation process takes a long time, while farmers want to sell cocoa beans quickly. This causes the selling price of cocoa beans to become low.